Progress in the Synthesis, Angiogenesis Activity and Mechanism of Chalcone Derivatives - Chen, Jie; Liu, Chen-Fu; Rao, Guo-Wu (Mini-Reviews in Organic Chemistry, 2020)
Cancer is a common disease that poses a serious threat to human health. Angiogenesis is essential for the growth and metabolism of tumors, providing oxygen and nutrition for the growth of cells and tissues. However, angiogenesis of tumors depends on the stimulation of growth factors. Vascular Endothelial Growth Factor (VEGFR) is the most unique factor. Therefore, VEGF/VEGFR targeting anticancer drugs are playing an increasingly significant role in clinical trials. In addition, it has been proved that chalcone, the precursor of natural flavonoids, has potential anti-tumor activity, especially anti-angiogenesis activity. This review summarizes the reports about the anti-angiogenesis of chalcone derivatives. Based on the chalcone skeleton, it is divided into substituted chalcones and modified chalcones. The anti-angiogenesis activities of natural or synthetic chalcones, benzene ring modified or connecting bridge modified chalcones are described in this review.
Keywords: chalcone